Trademark selection criteria for bad dental implants used by specialists. - Rivera Garcia, Carlos; Jojas Ortega, Juan; Casa Branca, Manoel Mario (Brazilian Journal of Implantology and Health Sciences, 2019)
Objective: Determine the most used selection criteria when choosing a brand of dental implants by specialist dentists. Material and method: If we identified the parameters for choosing an implant brand, we classified them into technical and market, sorting them into a closed-type questionnaire, valuing it by means of a psychometric scale from 1 to 5, plus an open question. It became a masterpiece for the convenience of twenty-one specialist dentists with less experience among three brands of implants. For the descriptive statistical analysis, Microsoft Excel 2011 version for Mac was used, using measures of central tendency such as Arithmetic and Fashion Media. The technical parameters were classified from 1st to 1st, marketing from 2nd to 2nd and suggested from p1 to p7. Results: The variability in prosthetic retention pillars, adequate availability of the products offered by the company and the compatibility of the additions between commercial brands, were the most relevant factors considered by specialists at the time of choosing a certain implant system. Conclusion: The reasons that influence the choice of an implant system are the variety and availability of products along with compatibility between brands.